Some Notes On The Terms Newspaper And Magazine And Their Features Of Difference - Vojtek, Juraj (Communication Today, 2025)
It is quite understandable that different dictionaries and manuals as well characterize the terms newspaper and magazine (periodical) in different ways. Anyway it is not quite understandable why these different ways are so different. That is why the paper has been leaned on a fact-ﬁnding. Its author has gone through different kind of dictionaries and manuals to ﬁnd out how the above mentioned terms are characterized. As for the dictionaries and encyclopaedias as well, they were of different kinds (e.g. language, general and specialized ones, in Czech, English, Polish and Slovak). The hypothesis, which was formulated by the author, stated that the most accurate would be the specialized dictionaries. But this assumption proved to be wrong and the most precise deﬁnitions of the two terms were found in an general encyclopaedia, namely Funk´s & Wagnalls New Encyclopedia.(31vo-lumes. New York : Funk & Wagnall Corporation, 1971–1993). On the pieces of knowledge found in the books, which the author went through, he formulates his own deﬁnitions of the terms newspaper and magazine and points out the signs (features) of difference between them. At the same time he underlines that any attempt of this kind is doomed, as the complexity of the terms cannot be put into a few words. Nevertheless we should try to be as accurate as possible.